The Advantages and Risks of AI in Sustainable Societal Development: Perspectives of Future Psychologists - Stoliarchuk, Olesia; Klishevych, Nataliia; Pavliuk, Roman; Tian, Lin; Binkivska, Kristina; Serhieienkova, Oksana; Strunhar, Аrtur; Divchuk, Tetiana (European Journal of Sustainable Development, 2025)
In the context of widespread psychological trauma among Ukrainian citizens, the education of future psychologists requires careful development of their professional competence and responsibility. Consequently, the nature and outcomes of artificial intelligence (AI) applications in the professional education of future psychologists pose a significant challenge for the national educational system due to the risks of academic integrity violations. A study involving 184 first- to fourth-year students highlighted the controversial role of AI in the professional education of future psychologists. Additionally, this study examines the role of AI in inventive activities, grounded in the theory and practice of inventive problem solving (TRIZ), exploring how AI fosters creative problem-solving and supports the development of innovative approaches in psychological practice. It was found that AI implementation in psychology students’ professional education is currently spontaneous and unregulated. The majority of surveyed students have repeatedly used AI for independent and qualification-related work, as well as for test assessments, without recognizing their actions as violations of academic integrity. Future psychologists identify several benefits of AI in their studies, including idea generation, information supplementation, systematization and structuring, and the rapid collection of relevant and useful data. However, common drawbacks include unreliable, misleading, or politically biased information, the absence of source citations, inaccurate data or procedural algorithms, and the occurrence of informational or visual hallucinations. The majority of respondents firmly believe that AI cannot fully replace psychologists, viewing it solely as an auxiliary tool. A positive finding is the students’ multifaceted understanding of AI’s applications in professional psychological practice. The majority of educators exhibit skepticism toward AI use in psychology education, while some avoid addressing the issue altogether. These findings indicate the need for educators to actively engage in discussions on the ethical and responsible use of AI by psychology students in their professional training. Given the spontaneous and unregulated integration of AI in Ukrainian higher education, a structured framework is necessary to ensure ethical implementation. Universities must develop clear guidelines and oversight mechanisms to balance innovation with academic integrity, preventing potential misuse while maximizing AI’s benefits in students’ professional development. In psychology education, where ethical considerations and human-centered approaches are paramount, it is essential to establish policies that regulate AI use, ensuring that it complements rather than compromises the development of essential professional competencies. This includes defining acceptable AI applications in academic work, implementing transparency measures, fostering critical AI literacy among both students and faculty, and encouraging AI-driven inventive activities — based on the theory and practice of inventive problem solving — that enhance students’ creative and analytical skills. Keywords: professional education, future psychologists, sustainable societal development, artificial intelligence (AI), academic integrity, inventive activities